2022
DOI: 10.3389/fped.2022.908542
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of exocrine pancreatic function in children and adolescents with direct and indirect testing

Abstract: The exocrine pancreas plays an important role in digestion. Understanding of the physiology and regulation of exocrine function provides insight into disease processes and basis of functional testing. Specifically, exocrine pancreatic insufficiency (EPI) can cause maldigestion and thus a proper assessment of exocrine pancreatic function is important. There are indirect and direct methods for evaluating pancreatic function. Indirect methods are varied and include stool, serum, urine, and breath tests. Fecal ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 151 publications
0
6
0
Order By: Relevance
“…Somatostatin, in addition to atropine, is a potent inhibitor of cholecystokinin (CCK)-mediated release of pancreatic enzyme secretion. CCK usually acts via the CCK receptor on pancreatic acinar cells, intrapancreatic neurons, and afferent cholinergic neurons ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin, in addition to atropine, is a potent inhibitor of cholecystokinin (CCK)-mediated release of pancreatic enzyme secretion. CCK usually acts via the CCK receptor on pancreatic acinar cells, intrapancreatic neurons, and afferent cholinergic neurons ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is often the first radiological test used to evaluate the pancreatic anatomy but computer tomography (CT), or magnetic resonance cholangiopancreatography (MRCP), specifically secretin-enhanced MRCP, are more helpful to better delineate the pancreatic anatomy such as pancreatic atrophy, pancreatic lipomatosis and evidence of chronic pancreatitis such as pancreatic ductal disruptions, parenchymal calcifications 106 , 107 ( Figure 1A-D ). In young children, the CT or MRCP testing may require deep sedation or anesthesia.…”
Section: Diagnosis Of Epimentioning
confidence: 99%
“…[9][10][11] Several studies have described the AAP phenotype and suggested underlying risk factors, which include older age at ALL diagnosis, higher cumulative dose of asparaginase, and certain host genome variants. [12][13][14][15][16] Potential long-term sequelae (e.g., organrelated symptoms, exocrine deficiency, and diabetes mellitus [DM]) could have a negative impact on growth, overall health, and quality of life, [17][18][19][20][21] however, this has not previously been systematically explored. Symptoms of pancreatic dysfunction may be unspecific and thus misinterpreted unless targeted screening is performed.…”
Section: Introductionmentioning
confidence: 99%